Post-crisis lesson for EMU governance from the principal-agent approach - Luca Barbone; Grzegorz Poniatowski (Center for Social and Economic Research (CASE), 2013)
This paper contributes to the ongoing debate on fiscal consolidation and the questionable effectiveness of the Stability and Growth Pact by addressing the problem of economic governance in the EMU with a game-theoretic principal-agent approach. Following the theory of delegation, we develop a principal-multi agent model where the EMU authorities act as a collective principal that designs contracts for each of two agents that reflect Europe's "South" and "North". We investigate what happens when agents face hidden-information moral hazard problem and when they are able to coordinate their actions. Bearing in mind the applicability of incentive mechanisms, we discuss the optimal contracts for the principal and each of the agents. We prove that the most efficient solution consists of tailor-made contracts, according to which highly indebted countries must be offered strong incentive mechanisms in the form of substantial penalties but also rewards (e.g., preferential loans). We also stress the importance of taking into account positive spillover effects, which could be facilitated by economic integration and fiscal policy coordination between the EMU Members.
Keywords: D82; E61; H60; 330; Moral Hazard; Principal-Agent; EU Economic Governance; Fiscal Compact; EU-Politik; Wirtschaftspolitik; Prinzipal-Agent-Theorie; Moral Hazard; Europäischer Stabilitätsmechanismus; Eurozone; EU-Staaten